Effects Of Exchange Rate Volatility On Real Estate Prices In Developing Economies, A Case Of Ghana - Adu Jack, John Kwame; Okyere, Frimpong; Amoah, Emmanuel K. S. (Advances in Social Sciences Research Journal, 2019)
This study aims to find out whether exchange rate volatility affects real estate domestic house prices in Ghana. To this end, a 32 years secondary data from World Development Indicators (WDI) and data from Real Estate Developers in Ghana are employed for the study. The study employs Autoregressive distributed lags (ARDL) bounds testing of cointegration t o test the null hypothesis that exchange rate volatility has n o impact on real estate housing prices. The study finds that real estate price is cointegrated with remittances, exchange rate and inflation. The long run equilibrium is stable and significant. Exchange rates d o not cause changes in real estate prices in both short and long run. Similarly past prices of real estate d o not have impact on current house prices. Rather, remittances positively cause real estate prices. Inflation on its part has a negative impact on real estate prices. It is therefore concluded that, volatility in the exchange rate between the cedi and other trading currencies does not predict changes in real estate prices.